Toxicity of Selected Insecticides against Cotton Mealybug (Phenacoccus solenopsis Tinsley) in Laboratory Bioassays - Padaliya, P. J.; Desai, H. R.; Bhanderi, G. R.; Patel, R. D. (International Journal of Economic Plants, 2022)
Investigations on susceptibility of insecticides in cotton mealybug (Phenacoccus solenopsis Tinsley) was carried out at Main Cotton Research Station, Navsari Agricultural University, Surat during October 2020 to January 2021 through the IRAC leaf dip bio-assay technique. Mealybug population from the farmer’s field of Bharuch district were collected and reared at Main Cotton Research Station, NAU, Surat under field cage cover. Leaf dip bio-assays were carried out for the seven insecticides viz., imidacloprid 70 WG, acetamiprid 20 SP, thiamethoxam 25 WG, buprofezin 25 SC, lamda cyhalothrin 5 EC, spinosad 45 SC and profenophos 50 EC with eight concentrations including control with three repetitions. At recommended rate, profenophos 50 EC at 0.1% and acetamiprid 20 SP at 0.004% recorded 83.50 and 80.77% mortality of mealybug after 72 hours of exposure. Buprofezin 25 SC at 0.05% recorded 78.89 while imidacloprid 17.8 SL at 0.00445% exhibited 67.70 and thiamethoxam 25 WG at 0.01% found to show 65.91% mortality of mealybug under laboratory bioassay after 72 hours of exposure.